Aplicación de un Adhesivo Autograbante y uso de la Técnica Incremental Oblicua para Resinas Compuestas en Restauraciones Directas en el Sector Posterior. Reporte de Caso - Lamas Lara, César (2013)
Nowadays we possess diverse materials to realize posterior direct restorations as the seventh-generation adhesives and the nanotechnology resins systems. As well as the materials are changing in the time the same happens with the techniques and protocols to use. In the present article there is detailed the protocol of application of seventh-generation adhesives as agent of link and the application of a composite resin using the oblique incremental technique in cavities with and without glass ionomer in the resolution of a clinical case. Results: The obtained results were satisfactory for the patient since it was possible to restore adequately the dental piece involved returning the aesthetics and the lost function. Conclusions: The deep knowledge of the materials to be used as well as the techniques it is going to lead to optimizing of our rehabilitation treatment.